As associações de interesse privado com foco na sustentabilidade : um estudo de caso sobre o grupo de trabalho da pecuária sustentável (GTPS) - Lima, Ana Carolinne Barata de (2017)
Faced with global challenges such as hunger and global warming, new demands have come to influence agricultural activities, among which is sustainability, which is a relevant dimension for Brazilian livestock activities and organizations in this industry to achieve market stability, they must adopt sustainable practices that meet institutional and stakeholder requirements. So, some AIPs have developed specific works focused on sustainability, which are passed on to their members who choose to adopt them in their products and processes, given the desire and need to rethink their impacts on society and the environment. This research seeks to analyze the role of AIPs in the adoption of sustainable practices in Brazilian livestock, from the single case with GTPS, a Vertical Association that acts specifically for this purpose, showing that its function goes beyond what the literature proposes. For this, this research follows the Single Case Study method, developed through the collection of data with semistructured interviews with specialists and secondary data with sustainability reports, which were analyze from the content analysis, with the support of the Atlas IT software. The main result of the study is that the role of AIPs such as GTPS is to coordinate the chain in favor of collective goods that go beyond the strategic ones, given that these assets surround sustainability and not only the interests of its members. In addition, it was possible to arrive at an analytical model based on the advance of theories of sustainability, institutional environment, strategy, private interest associations and willingness to adopt. This dissertation contributes to the deepening of the literature, as well as to show the possibility of replicating the practices that are use in livestock for other areas as important as global sustainable development.